The Professional Quality of Life of Nurses who Work in the Intensive Care Unit and Emergency Unit - Astri Eka Wulandari; F. Sri Susilaningsih; Irman Somantri (Universitas Padjadjaran, 2018)
Nurses need compassion when providing health services. Compassion felt by nurses can be Compassion Satisfaction (positive aspects) and Compassion Fatigue (negative aspects), and may affect nursing care and Nurses’ Professional Quality of Life. The tendency to negative aspects will be felt by the nurses themselves, patients and hospitals. The purpose of this study was to determine the quality of life of professionals (Professional Quality of Life) nurses in the Intensive Care Unit (ICU) and Emergency Room (ER) of the Kota Bandung Hospital. This research was a quantitative descriptive study. Involving 62 nurses from ICU and ER through total sampling technique with a response rate of 97%. Data was collected using Professional Quality of Life (ProQol) version 5 then analyzed with descriptive statistics. The results showed that 20.97% had a positive Professional Quality of Life according to the Stamm combination interpretation while outside of Stamm's interpretation, 32.26% tended to be positive. According to the results of the average score of each sub-variable, Compassion Satisfaction was in the medium category. The highest average score of compassion satisfaction was ICU nurses, the highest secondary traumatic stress was PICU/NICU nurses and the highest average score of burnout was emergency nurses. Hospitals need to conduct regular reviews of nurse Professional Quality of Life and conduct counseling programs for nurses who have ProQol towards negative and risky aspects.